AN ANALYSIS OF THE ROLE OF TAX PLANNING AND DEFERRED TAX ASSETS IN EARNINGS MANAGEMENT IN THE BANKING INDUSTRY - Wirda Muhibbatul Lubabah; Sari Andayani (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to assess and empirically prove the independent variables of tax planning and deferred tax assets affecting the dependent variable of earnings management. This research employs a quantitative approach based on an associative design, formulating hypotheses and applying inferential statistical procedures to evaluate causal relationships, using purposive sampling involving a number of companies and observational data taken from annual audit reports. The analysis results indicate that tax planning has a significant influence on earnings management. Conversely, deferred tax assets do not show a significant effect. These findings suggest that the long-term orientation and limitations in the flexibility of deferred tax assets substantially reduce their effectiveness as instruments for short-term earnings manipulation.